Pemanfaatan Teknologi Internet of Things untuk Penunjang Model Pembelajaran Science, Technology, Engineering and Mathematics - Budianto, Akhmad Ghiffary; Zulkarnain, Andry Fajar; Suryo, Arief Trisno Eko; Cahyono, Gunawan Rudi; Rusilawati, Rusilawati; Wibowo, Bayu Setyo; Az-Zahra, Siti Fathimah; Atmadja, Fridho Ery Dwi; Najua, Siti Nur (Indonesian Journal for Social Responsibility, 2025)
The development of outstanding human resources can be achieved through the application of Science and Technology (S&T) in education. The focus of applying S&T is on the Science, Technology, Engineering, and Mathematics (STEM) learning approach. The STEM learning approach equips students with the ability to think creatively, critically, and problem-solving oriented, as well as to work collaboratively in teams, adapt to technological advancements, and continue to innovate. A lack of examples regarding the methods and applications of the latest technology in STEM fields poses a problem for students in schools. Students often struggle with understanding theories due to the absence of engaging demonstrative examples. The use of the Internet of Things (IoT) in various fields and daily life serves as an example of STEM application. Introducing IoT in several science subjects such as Physics, Chemistry, Biology, and Mathematics can provide engaging and relevant learning experiences. The goal of this Community Service activity is to provide an introduction and examples of IoT application as a supporting model for STEM learning at SMAN 1 Banjarbaru. The method used involves socializing IoT technology and including practical applications of IoT in STEM fields, such as assembling IoT kit components with WeMos D1, ESP32 NodeMCU, and various sensors for measuring temperature and pH. It is expected that students will understand the application of the latest IoT technology in STEM fields. Additionally, the school will be able to provide engaging, up-to-date learning experiences in technology that are relevant to the latest curriculum. As the result, three groups of students, each consisting of five members, successfully developed an IoT system for measuring liquid temperature and pH.